Modeling and design optimization of reclaimed asphalt pavement containing crude palm oil using response surface methodology. (12th July 2021) - Rafiq, Waqas; Napiah, Madzlan; Habib, Noor Zainab; Sutanto, Muslich Hartadi; Alaloul, Wesam Salah; Khan, Muhammad Imran; Musarat, Muhammad Ali; Memon, Abdul Muhaimin
Highlights: The effect of different percentages of (RAP) and crude palm oil (CPO). Statistical Analysis for designing and analyzing the experimental results. A microstructure level investigation using AFM and FTIR analysis. Crude palm oil inclusion in HMA-RAP showed good improvement. Abstract: This study discusses the influence of using crude palm oil in hot mix asphalt incorporating recycled asphalt pavement materials. The effect of different percentages of recycled asphalt pavement (RAP) and crude palm oil (CPO) on stability, flow, stiffness, voids in mix (VIM), voids filled with asphalt (VFA), and Indirect Tensile Strength (IDT) were assessed. In addition, for the statistical analysis an analytical tool response surface methodology (RSM) was used for designing and statistically analyzing the experimental results. A microstructure level investigation on the virgin binder (60/70) and RAP binder incorporating crude palm oil was performed using atomic force microscopy (AFM) and Fourier transform infrared spectroscopy (FTIR) analysis. Experimental results showed that stability and indirect tensile strength increases with an increase in recycled asphalt pavement material up till 80%. However, 100% RAP with crude palm oil resulted in reduction in these strength parameters. The microstructural analysis shows that the incorporation of CPO in virgin and RAP aged binder change the structure of aged and virgin binder by new and unique phase formations. The statistical models were found significant and well fitted on bases of R 2 value (>0.80), high adequate precision value (>4), low p-value and insignificant lack-of-fit. Furthermore, ANOVA model theoretical results by the RSM analysis were validated by experiments with <5% of error that represent a good agreement between experimental and theoretical results. Crude palm oil inclusion in HMA-RAP showed good improvement in performance parameters indicating a potential source of rejuvenating agent as bio binder material for the pavement construction industry.